1980
DOI: 10.1056/nejm198001313020505
|View full text |Cite
|
Sign up to set email alerts
|

Liver Transplantation for Advanced Liver Disease with Alpha-1antitrypsin Deficiency

Abstract: Alpha-1-antitrypsin deficiency associated with chronic obstructive airway disease was recognized in 1963 by Laurell and Ericksson. 1 In 1969, Sharp 2 described the first cases of alpha-1-antitrypsindeficiency disease in children with cirrhosis. Since then, this inborn error has been recognized as one of the more common factors in cirrhosis of infancy and childhood, 3 including "neonatal hepatitis." 4 Alpha-1-antitrypsin is a glycoprotein that accounts for a major portion of the alpha-1 globulin fraction of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0
1

Year Published

1982
1982
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(35 citation statements)
references
References 25 publications
1
33
0
1
Order By: Relevance
“…Liver transplantation has been shown to correct the metabolic defect in AAT deficiency, and as in our case, results in the conversion of the patients' phenotype from ZZ to MM after successful transplantation (22).…”
Section: Discussionsupporting
confidence: 58%
“…Liver transplantation has been shown to correct the metabolic defect in AAT deficiency, and as in our case, results in the conversion of the patients' phenotype from ZZ to MM after successful transplantation (22).…”
Section: Discussionsupporting
confidence: 58%
“…Studies of changes in a,-AT allotypes after orthotopic liver transplantation have shown that liver is the predominant site of synthesis of blood-borne a,-AT (2,3). There is evidence for extrahepatic sites ofsynthesis, notably that in blood monocytes and tissue macrophages (4).…”
mentioning
confidence: 99%
“…Liver is the predominant site of synthesis (5,6), but human monocytes and macrophages also synthesize and secrete a1PI (7). Furthermore, the cellular defect in homozygous PiZZ aPI deficiency, a selective decrease in rate of secretion of aPI, is expressed in human monocytes from PiZZ individuals (8).…”
mentioning
confidence: 99%